Determination of Consumer Purchase Decisions In The E-Commerce Ecosystem - Abi Surya Wijaya; Adelia marta viani (Politeknik Siber Cerdika Internasional, 2026)
This study aims to analyze the determination of consumer purchase decisions in the e-commerce ecosystem in Indonesia, by examining the influence of price variables, product quality, consumer trust, online reviews, and ease of use of the platform simultaneously or partially. Indonesia's rapid e-commerce development with a transaction value of USD 59 billion in 2023 creates an urgent need to understand the factors that determine digital consumer purchasing decisions. The study used a quantitative approach with a cross-sectional survey design. The population is active e-commerce consumers aged 17–45 years in the West Java region, with a sample of 360 respondents determined using purposive sampling techniques. Data were collected through a 5-point Likert scale structured questionnaire and analyzed using multiple regression with the help of SPSS 26. The results showed that the five independent variables simultaneously had a significant effect on purchasing decisions (F = 152.47; p < 0.001) with a determination coefficient of R² = 0.681, meaning that 68.1% of the variation in purchasing decisions was explained by the five variables. Partially, consumer confidence had the greatest influence (B = 0.341; p < 0.001), followed by price (B = 0.312), ease of use (B = 0.289), product quality (B = 0.278), and online reviews (B = 0.256). The novelty of the research lies in the integration of the five determinant factors in one analytical model tested in the context of Indonesian e-commerce multi-platform. These findings provide strategic implications for e-commerce businesses to prioritize building trust and optimizing user experience in designing digital marketing strategies.